DREAMING ARCHITECTURE WITHOUT ARCHITECTS: DESIGNERS/BUILDERS OF THEIR OWN “HOMES” - TUZTASI, Ugur (Acta Scientiae et Intellectus, 2024)
Throughout history construction of “homes” always existed at the borders of architecture be it with or without architects. This study explores the efforts of an artisan who preferred to build his own “home”. Mustafa Hızır has deposited his architectural desires in every corner of the “home” he constructed in 33 years in Niğde. Although his efforts are not as colourful as the dreams of Antoni Gaudí or Jacques Couëlle, the architect of Happiness Homes or unorthodox architect Friedensreich Hundertwasser, the story of this artisan in dreaming and building his “home” is very interesting. “Home” means “hearth” for Hızır and he was inspired by birds' nests while building his “home”. Hızır, who has spent more than thirty years building his “home” investigating crossbill nests, has hand-crafted all the items in his “home” from furniture to chandeliers. In short, this study explores the interesting story of Mustafa Hızır's “home” and along with stories from other artisans who realised their architectural dreams in their “homes”.